(X-3)+(X-7)=
-4(x+2)-(2x+2)=
2(x+6)-(x-3)=
-3(2x+6)-(x+5)=
3(x-5)-(2x+9)=
2(x+12)-(x-6)=
(2x-1)-(x+12)=
(9x-5)+(x-9)=
-(x-6)-(2x-14)=
-(2x-5)+3(x+1)=
-(x-9)-3(x-2)=
(x-7)-2(x+1)=
(x+12)+3(x-1)=
-(3x-7)-(4x+5)=
-(x-8)+3(x-7)=
-(2x+2)-2(2x-1)=
-(x-3)-(3x+2)=
2(x-8)+(6x+3)=
3(3x-2)-2(x-7)=
-2(x+4)+(x-2)=
4(2x-9)+2(x+3)=
-3(x-3)+8(x-3)=
2(x+2)+3(x-5)=

2

Odpowiedzi

2010-03-04T15:29:16+01:00
(X-3)+(X-7)=x-3+x-7=2x-10
-4(x+2)-(2x+2)=-4x-8-2x-2=-6x-10
2(x+6)-(x-3)=2x+12-x+3=x+15
-3(2x+6)-(x+5)=-6x-18-x-5=-7x-23
3(x-5)-(2x+9)=3x-15-2x-9=x-24
2(x+12)-(x-6)=2x+24-x+6=x+30
(2x-1)-(x+12)=2x-1-x-12=x-13
(9x-5)+(x-9)=9x-5+x-9=10x-14
-(x-6)-(2x-14)=-x+6-2x+14=-3x+20
-(2x-5)+3(x+1)=-2x+5+3x+3=x+8
-(x-9)-3(x-2)=-x+9-3x+6=-4x+15
(x-7)-2(x+1)=x-7-2x-2=-x-9
(x+12)+3(x-1)=x+12+3x-3=4x+9
-(3x-7)-(4x+5)=-3x+7-4x-5=-7x+2
-(x-8)+3(x-7)=-x+8+3x-21=2x-13
-(2x+2)-2(2x-1)=-2x-2-4x+2=-6x
-(x-3)-(3x+2)=-x+3-3x-2=-4x+1
2(x-8)+(6x+3)=2x-16+6x+3=8x-13
3(3x-2)-2(x-7)=9x-6-2x+14=7x+8
-2(x+4)+(x-2)=-2x-8+x-2=x-10
4(2x-9)+2(x+3)=8x-36+2x+6=10x-30
-3(x-3)+8(x-3)=-3x+9+8x-24=5x-15
2(x+2)+3(x-5)=2x+4+3x-15=5x-11
Najlepsza Odpowiedź!
2010-03-04T15:32:59+01:00
(X-3)+(X-7)= x-3+x-7 = 2x-10

-4(x+2)-(2x+2)= -4x-8-2x-2 = -6x-10

2(x+6)-(x-3)= 2x+12-x+3 = x+15

-3(2x+6)-(x+5)= -6x-18-x-5 = -7x-23

3(x-5)-(2x+9)= 3x-15-2x-9 = x-24

2(x+12)-(x-6)= 2x+24-x+6 = x+30

(2x-1)-(x+12)= 2x-1-x-12 = x-13

(9x-5)+(x-9)= 9x-5+x-9 = 10x-14

-(x-6)-(2x-14)= -x+6-2x+14 = -3x+20

-(2x-5)+3(x+1)= -2x+10+3x+3 = x+13

-(x-9)-3(x-2)= -x+9-3x+6 = -4x+15

(x-7)-2(x+1)= x-7-2x-2 = -x-9

(x+12)+3(x-1)= x+12+3x-3 = 4x+9

-(3x-7)-(4x+5)= -3x+7-4x-5 = -7x+2

-(x-8)+3(x-7)= -x+8+3x-21 = 2x-13

-(2x+2)-2(2x-1)= -2x-2-4x+2 = -6x

-(x-3)-(3x+2)= -x+3-3x-2 = -4x+1

2(x-8)+(6x+3)= 2x-16+6x+3 = 8x-13

3(3x-2)-2(x-7)= 9x-6-2x+14 = 7x+8

-2(x+4)+(x-2)= -2x-8+x-2 = -x-10

4(2x-9)+2(x+3)= 8x-36+2x+6 = 10x-30

-3(x-3)+8(x-3)= -3x+9+8x-24 = 5x-15

2(x+2)+3(x-5)= 2x+4+3x-15 = 5x-11